"If the bullet in the forehead ...": about manipulative tactics of new phraseologisms of an idiomatic character - Syzonov, Dmytro (Current issues of Ukrainian linguistics: theory and practice, 2025)
The article defines manipulative tactics and strategies used in media with the help of a stylistic potential of a new phraseology. The author argues that one of the bases for the formation of socio-political reality with the help of media discourse is the creation of images of political figures, the formation of which occurs in the process of involving into political communication various stylistic means, particularly, different types of phraseologisms. On the example of A. Yatsenyuk’s speech an analysis of phraseologisms which influence the potential electorate is given. The new political phraseology arises due to extralinguistic factors, among which particularly important are the Orange Revolution of 2004 and the Revolution of Dignity of 2014. An innovative phraseology that emerges in connection with the development of world socio-political events, election campaigns, description of military conflicts etc. is analyzed. On the example of a vivid phraseologism of an idiomatic character “If a bullet in the forehead, then a bullet in the forehead”, expressed by A. Yatsenyuk during the Euromaidan, the models of a successful use of a phraseologism / a transformed phraseologism in political media for different purposes, primarily manipulative, are shown. It is proved that the new phraseology is the most productive specifically in political media, as it acts not on an individual, but on a mass recipient. Among the most effective manipulative tactics in political media, where the innovative phraseology is used, are glittering generalities tactics, name calling tactics, semantic transfer tactics, verbal allusion tactics etc. The role of phraseological innovations within these tactics is so high that journalists who use them achieve not so much informational but a manipulative-strategic target.